Bariatric surgery reduces CD36-bearing microvesicles of endothelial and monocyte origin - Jaco Botha; Morten Hjuler Nielsen; Maja Høegh Christensen; Henrik Vestergaard; Aase Handberg (Nutrition & Metabolism, 2018)
Abstract Background Bariatric surgery is a widely adopted treatment for obesity and its secondary complications. In the past decade, microvesicles (MVs) and CD36 have increasingly been considered as possible biomarkers for obesity, the metabolic syndrome (MetSy), type 2 diabetes mellitus (T2DM). Thus, the purpose of this study was to investigate how weight loss resulting from bariatric surgery affects levels of specific MV phenotypes and their expression of CD36 scavenger receptor. Additionally, we hypothesised that subjects with MetSy had higher baseline concentrations of investigated MV phenotypes. Methods Twenty individuals undergoing Roux-en-Y gastric bypass surgery were evaluated before and 3 months after surgery. MVs were characterised by flow cytometry at both time points and defined as lactadherin-binding particles within a 100-1000 nm size gate. MVs of monocyte (CD14) and endothelial (CD62E) origin were defined by cell-specific markers, and their expression of CD36 was investigated. Results Following bariatric surgery, subjects incurred an average BMI reduction (delta) of − 8.4 ± 1.4 (p < 0.0001). Significant reductions were observed for the total MVs (− 66.55%, p = 0.0017) and MVs of monocyte (− 36.11%, p = 0.0056) and endothelial (− 40.10%, p = 0.0007) origins. Although the bulk of CD36-bearing MVs were unaltered, significant reductions were observed for CD36-bearing MVs of monocyte (− 60.04%, p = 0.0192) and endothelial (− 54.93%, p = 0.04) origin. No differences in levels of MVs were identified between subjects who presented with MetSy at baseline (n = 13) and those that did not (n = 7). Conclusion Bariatric surgery resulted in significantly altered levels of CD36-bearing MVs of monocyte and endothelial origin. This likely reflects improvements in ectopic fat distribution, plasma lipid profile, low-grade inflammation, and oxidative stress following weight loss. Conversely, however, the presence of MetSy at baseline had no impact on MV phenotypes.